REVIEW OF THE MONOGRAPH TOTSKA O. L. MANAGING THE DEVELOPMENT OF HIGHER EDUCATION OF UKRAINE IN EUROPEAN EDUCATIONAL AREA (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Monograph "Management of the development of higher education of Ukraine in the European educationalspace "will be useful both for scientists, students, teachers interested in processesManaging the development of higher education in Ukraine in the context of the functioning of the European Spacehigher education, and for practitioners involved in the management of higher educational institutions.
Keywords: higher education, development management, educational institution